Manajemen Keuangan Pada Lembaga Pendidikan Bina Anak Sholeh Yogyakarta - Denas Hasman Nugraha (STAI Terpadu Yogyakarta, 2022)
Islamic educational institutions are currently developing very quickly as a result of public interest and growing public confidence in these institutions. One of the many educational institutions in Yogyakarta with a network of schools at various levels is the Educational Institution for Bina Anak Sholeh Yogyakarta. Batita, Play Group, Integrated Islamic Elementary School, Integrated Islamic Junior High School, and Integrated Islamic High School are some of the current levels. This study combined a descriptive method with a qualitative approach as its research methodology. For the implementation of operations at each level to be successful, financial management must be done in an organized and orderly fashion. Where financial management becomes crucial due to its role in carrying out educational activities. The primary finding of this study may be noticed in the financial management realization, planning, and supervision phases. At the Islamic Education Institution of Bina Anak Sholeh Yogyakarta, financial management planning is executed in the form of a RAPBS that is put together by all leaders at each level based on that levels' needs while still referencing the school's vision and mission. The implementation of financial management at the Islamic Education Institution of Bina Anak Sholeh Yogyakarta has been modified to the technical guidelines listed in the RAPBS for that year and is used for expenditures on school interests, practice materials, practical tools, financing student activities, and developing the quality of students and teachers. Fairness and efficiency have also been applied to the management of school finances. An honest and reliable public accountant was used to oversee the financial administration at the Islamic Educational Institution of Bina Anak Sholeh Yogyakarta. Reports are produced in compliance with the regulations that are in effect